Biotransformation and inhibition effects of hexachlorocyclohexanes during biogas production from contaminated biomass characterized by isotope fractionation concepts. (February 2018) - Lian, Shujuan; Nikolausz, Marcell; Nijenhuis, Ivonne; Francisco Leite, Athaydes; Richnow, Hans Hermann
Highlights: Different concentrations of hexachlorocyclohexane were tested in biogas reactors. High concentration of hexachlorocyclohexane result in inhibition on CH4 production. Carbon isotope composition of CH4 can be used to monitor the methanogenic pathway. Carbon isotope fractionation factors indicated reductive dechlorination. Abstract: Hexachlorocyclohexane (HCH) production for pesticides was banned by Stockholm Convention (2009) due to its harmful and adverse effects on the environment. Despite this measure, many areas contaminated with former HCH production-waste products still require management. As a potential solution contributing to clean-up of these sites, anaerobic digestion (AD) of pesticide-contaminated biomass to produce biogas is a promising strategy. High pesticide concentrations, however, may inhibit biogas production. Therefore, laboratory-scale batch reactors were set up to investigate biogas reactor performance in presence of HCH. Inhibitory effects on biogas yield was observed with concentrations of HCH ≥ 150 mg/L. Carbon isotope composition of methane (δ 13 CCH4 ) showed significant fluctuation after an inhibition phase, indicating that HCH toxicity can affect the activity of acetoclastic methanogens. Furthermore, combined results of metabolites and carbon isotope fractionation factors (εc ) demonstrated that α- and γ-HCH can be degraded to chlorobenzene and benzene via anaerobic reductive dechlorination.